The Portrayal of Female Nurse in the Poetry of John Keats - Azeez, Hawzhin H.; Al-Jumaili, Asst. Prof. Dr. Yasir (Mitanni Journal of Humanitarian Sciences, 2024)
In his works, John Keats describes female characters variously; they range from the evil seductress of the La Bell Dame Sans Merci and Lamia to the innocent pure Madeline of The Eve of St. Agnes and innocent Isabella of The Pot of Basil. This study continues the tradition of investigating female characters in Keats’s poetry. It examines the depiction of the female nurse in selected poems of John Keats. The study provides interesting observation about the representation of this type of female figure. There is little research about the image of female nurse Romantic poetry. Therefore, this study attempts to see how female nurses are featured in Keats’s poetry. Understanding the way in which nurses were depicted is very important for two reasons: first, it provides a glimpse into the public image of female nurse during Keats’s time. Second, it allows seeing whether Keats had created the image of female nurse based on his daily observations of actual nurses in the medical school or he had created his own stereotype. The study would contribute to the existing literature of women characters in Keats’s poetic works. Key Words: Female nurse, John Keats, romantic poetry, medical humanities, female healers.